PROSPEK PENGEMBANGAN INTEGRASI LIMBAH PERTANIAN DAN PEMELIHARAAN MAGGOT BLACK SOLDIER FLY SEBAGAI PAKAN AYAM KAMPUNG DI DESA BULUSARI BANYUWANGI - Sefri Ton; Mohamad Ilham Hilal; Danang SWPJ Widakdo (Politeknik Pertanian Negeri Kupang, 2021)
This study aims to analyze development prospects and calculate the benefits of integrating agricultural waste and maintaining Black Soldier Fly maggot as free range chicken feed in Bulusari Village. Primary data was carried out by interview and descriptive analysis. Meanwhile, Secondary data were collected from journal references and government agencies. The results showed the potential for household household organic waste, chicken manure and cow dung, were 3,000 kg, 359.3 kg, and 10,315 kg respectively. Other sources of waste can be obtained From nearby market, which is about 5-10 km from Bulusari Village. The advantage of raising free-range chickens by processing agricultural waste and maintaining BSF maggots can save 68.5% on feed purchases. Another advantage of maintaining maggot is by selling prepupa at a price range of Rp. 75,000 - Rp. 80,000 per kilogram. This research can be concluded that the development of integrated agricultural waste through maggot maintenance can increase community income and produce zero waste. Keywords: BSF Maggots, Free-range chicken feed, Integration, Waste agricultural